(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2008)
Deregulation of power industry has made us think over the transmission loss allocation to network users and to various interconnected transactions including bilateral one. It is an important issue to be solved exactly. Because of the non-linear nature of power flow and power loss, it is very difficult to segregate and to allocate losses among the participants properly. This paper presents an instantaneous loss allocation algorithm including DC-Optimal Power Flow. Using Incremental Transmission Loss (ITLs) factors and the power outputs of generators, we have calculated preliminary loss to each generator. Calculating loss allocation rates from the preliminary losses, the final loss allocation has been done (according to loss allocation rate) to meet the total loss calculated by DC-OPF. The effectiveness of this procedure has been studied for a small model power system and also for the IEEE-118-bus system. Keywords: Transmission loss allocation, DC optimal power flow, Deregulated power market, Bilateral transactions. Bangladesh J. Sci. Ind. Res. 42(3), 249-256, 2007